Analisis permasalahan pelaksanaan pembelajaran jarak jauh di sekolah dasar - Rahmawati, Silfira; Mulyono, Hadi; Istiyati, Siti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to analyze and provide solutions to problems that arise during distance learning (PJJ) at SD Negeri Soropadan No. 108 Surakarta. This study uses a qualitative research method. Data were obtained through research subjects, namely homeroom teachers, students, observations result, and documents. The data collection technique used in thin research is interview homeroom teachers, students with questionnaires, observation, and other supporting document. A research is needed, namely an observation guide sheet, interview guide sheet, and questionnaire sheet. The data validity test uses the triangulation method. The data were analyzed using the Miles and Huberman model. The problem of implementing learning is the lack of self-preparation of teachers, lack of teacher's, knowledge related to distance learning technology so that learning is monotonous, lack of, interaction during learning, students who do not do assignments, lack of feedback to students, a lack of monitor student assignments, teachers providing material, delays in collecting assignments, limitations of learning technology used, obstacles in using google forms. The solution to the problemis to take part in socialization or training regarding distance learning, then create more diverse and fun learning, change the media from learning video or short messages to video calls so that interaction is maximized, students who do not do assignments are given warnings, a longer time or reduced points according to the length of the delay, provide simple support and appreciation after submitting assignments, changing the lesson plan to reduce the material to be taught, the teacher supervising the assignment of students, the teacher explains the material provided via voice messages or else, share material before learning, or use media that is more supportive of sharing screens, tutorials or procedures for using google forms.